2018
DOI: 10.3390/ijms19123705
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Regulators of Insulin Signaling: Research Updates and Potential Therapeutic Perspectives in Type 2 Diabetes

Abstract: The insulin signaling pathway is composed of a large number of molecules that positively or negatively modulate insulin specific signal transduction following its binding to the cognate receptor. Given the importance of the final effects of insulin signal transduction, it is conceivable that many regulators are needed in order to tightly control the metabolic or proliferative functional outputs. MicroRNAs (miRNAs) are small non-coding RNA molecules that negatively modulate gene expression through their specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 165 publications
(173 reference statements)
3
58
0
2
Order By: Relevance
“…The roles of the IR and IR/IGF-IR were reviewed, along with their association with ncRNAs in regulating DM and cancer [25,116]. We discussed a number of well-known miRNAs and lncRNAs that regulate IGF-1R signaling in DM and cancer, and further highlight the potential underlying molecular pathogenesis of their comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of the IR and IR/IGF-IR were reviewed, along with their association with ncRNAs in regulating DM and cancer [25,116]. We discussed a number of well-known miRNAs and lncRNAs that regulate IGF-1R signaling in DM and cancer, and further highlight the potential underlying molecular pathogenesis of their comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The principal therapeutic approach is to restore miRNAs that target and downregulate the IGF-1R expression and/or signaling during the development of DM, which is extensively discussed in previous reviews [116,117]. Delivering miRNA directly or using exogenous recombinant viral vectors are two common therapeutic approaches under development.…”
Section: Discussionmentioning
confidence: 99%
“…Direct inactivation of AKT is mediated by protein phosphatase 2a (PP2A) [162]. PP2A activity has been shown to be increased in primary rat hepatocytes in insulin resistance condition [163]. Interestingly, insulin resistant Zucker Diabetic Fatty rats, PP2A mRNA is increased in liver, muscle and adipose tissue, thus suggesting a role for the phosphatase in deregulating insulin signaling in T2DM [163].…”
Section: Modulation Of the Insulin Signaling Pathwaymentioning
confidence: 99%
“…Multiple studies have shown that miRNAs are pivotal regulators of different aspects of glucose homeostasis, such as peripheral insulin signaling [4], β cells function [5], and phenotype maintenance [6,7].…”
Section: Introductionmentioning
confidence: 99%